Qualitative Study of Household Livelihood Strategies and Constraints in Zambia - Poulin, Michelle; Bomuhangi, Allan (World Bank, Washington, DC, 2018)
Inclusive growth and poverty reduction requires an understanding of the constraints to increasing productivity of the informal sector, which employs the majority of Zambians. Zambians working in this sector are poor, have little education, die young from avoidable diseases, and live predominantly in rural areas. Even if more opportunities for formal employment currently existed, this population would not be qualified for these jobs. Their productive inclusion in society, and making sure they can invest in their children’s futures to break the intergenerational transmission of poverty, requires rural investment that can help unlock constraints to informal sector productivity. A recent review of the constraints that women face, relative to men, reveal that women’s business performance is affected by a combination of contextual factors and gender differences. This qualitative study sought to understand : (a) the key livelihood strategies used by women and men in Zambia; (b) the key constraints that women and men face; (c) how these constraints shape the strategies that are available; and (d) what women and men understand about human rights. The research had a specific focus on identifying responses that could help to increase women’s economic empowerment.